Tax Administration Reform and Fiscal Adjustment : The Case of Indonesia (2001-07) - Brondolo, John (IMF Working Papers; Working Paper, 2008)
Tax administration reforms can play an important role in fiscal adjustment. This role is examined by reviewing Indonesia's tax reform cum fiscal adjustment experience since 2001. The paper describes Indonesia's fiscal adjustment strategy, its tax administration reforms, and assesses the impact of these reforms on fiscal adjustment. Evidence suggests tax administration improvements had a strong positive impact on the tax yield and a positive effect on the investment climate. Lessons are presented for designing tax administration reforms within the context of a fiscal adjustment program and reform priorities are identified for Indonesia's ongoing efforts to strengthen tax administration.